Rethinking the Atlantic World - Albertone, Manuela. author. aut Link
XI, 308 p.
Keywords: This unique collection of essays provides a re-evaluation of the term 'Atlantic', by placing at the core of the debate on republicanism in the early modern age the link between continental Europe and America, rather than assuming British political culture as having been widely representative of Europe as a whole.